Autonomic neuropathy and gallbladder motility in patients with liver cirrhosis - Kul, Kemal; Serin, Ender; Yakar, Tolga; Coşar, Arif Mansur; Özer, Birol (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Impaired gallbladder motility has been suggested as a contributor to increased incidence of gallstones in patients with liver cirrhosis. The purpose of this study was to determine gallbladder function and its relation with autonomic neuropathy in liver cirrhosis. Materials and Methods: Gallbladder function was measured using ultrasonography in 48 patients with liver cirrhosis and in 31 controls. Autonomic neuropathy tests were applied in patients with liver cirrhosis. Patients with liver cirrhosis were analyzed in subgroups according to the severity of disease using the Child-Pugh classification. Results: Fasting gallbladder volume was 16.2 mL (range: 2.1 mL-71.9 mL) in patients and 17.6 mL (range: 4.9 mL-76.6 mL) in controls. There were no differences in fasting gallbladder volume among the study groups (p>0.05). Gallbladder ejection fraction was significantly higher in patients compared with controls (84% vs. 65%) (p<0.001). No correlation was found between gallbladder ejection fraction and autonomic neuropathy (p>0.05). Conclusion: Our results indicate that liver cirrhosis does not impair gallbladder emptying, and that there is no association between gallbladder motility and autonomic neuropathy. Further investigations are required to explain increased gallbladder motility in liver cirrhosis.